Clinical Features of Lysosomal Acid Lipase Deficiency - Burton, Barbara K; Deegan, Patrick B; Enns, Gregory M; Guardamagna, Ornella; Horslen, Simon; Hovingh, Gerard K; Lobritto, Steve J; Malinova, Vera; McLin, Valerie A; Raiman, Julian; Di Rocco, Maja; Santra, Saikat; et al. (Journal of pediatric gastroenterology and nutrition, 2015)
OBJECTIVE: The aim of this study was to characterize key clinical manifestations of lysosomal acid lipase deficiency (LAL D) in children and adults. METHODS: Investigators reviewed medical records of LAL D patients ages ≥5 years, extracted historical data, and obtained prospective laboratory and imaging data on living patients to develop a longitudinal dataset. RESULTS: A total of 49 patients were enrolled; 48 had confirmed LAL D. Mean age at first disease-related abnormality was 9.0 years (range 0-42); mean age at diagnosis was 15.2 years (range 1-46). Twenty-nine (60%) were male patients, and 27 (56%) were <20 years of age at the time of consent/assent. Serum transaminases were elevated in most patients with 458 of 499 (92%) of alanine aminotransferase values and 265 of 448 (59%) of aspartate aminotransferase values above the upper limit of normal. Most patients had elevated low-density lipoprotein (64% patients) and total cholesterol (63%) at baseline despite most being on lipid-lowering therapies, and 44% had high-density lipoprotein levels below the lower limit of normal. More than half of the patients with liver biopsies (n = 31, mean age 13 years) had documented evidence of steatosis (87%) and/or fibrosis (52%). Imaging assessments revealed that the median liver volume was ∼1.15 multiples of normal (MN) and median spleen volume was ∼2.2 MN. Six (13%) patients had undergone a liver transplant (ages 9-43.5 years). CONCLUSION: This study provides the largest longitudinal case review of patients with LAL D and confirms that LAL D is predominantly a pediatric disease causing early and progressive hepatic dysfunction associated with dyslipidemia that often leads to liver failure and transplantation.
Keywords: Fatty Liver; aspartátaminotransferasy; játra; Wolmanova nemoc; Lipase; Cholesterol; Humans; Longitudinal Studies; cholesterol; lidé středního věku; dítě; Aspartate Aminotransferases; jaterní cirhóza; Child; Wolman Disease; Female; mladý dospělý; dospělí; Alanine Transaminase; Sterol Esterase; nemoc ze střádání esterů cholesterolu; lidé; Liver Cirrhosis; ztučnělá játra; Liver Transplantation; předškolní dítě; transplantace jater; slezina; Adult; Cholesterol Ester Storage Disease; ženské pohlaví; longitudinální studie; sterolesterasa; Liver; Male; Middle Aged; Adolescent; Spleen; Young Adult; alanintransaminasa; mužské pohlaví; prospektivní studie; Child, Preschool; mladiství; lipasa; Prospective Studies